(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The system of international relations in the 21st century increasingly redefines several key geopolitical concepts. The global geopolitical model today is also being reshaped on international level. Along with these new geopolitical trends, new interpretations of concepts such as war, conflict, and use of force have emerged. The main purpose of this paper is to analyze the tools and strategies for resolving the so-called "hybrid conflicts". The main thesis of the research is that in order to resolve such a conflict it is necessary to apply the whole set of instruments at both military and strategic level. Otherwise, this type of conflict can be a serious threat to the national security of each country. To prove his thesis, the article sets the following tasks. First, to analyze the concept of hybrid conflict and clarify its essence. Second, to systematize the main geopolitical aspects of the hybrid conflicts. Third, to launch possible techniques and strategies for the resolution of hybrid conflicts. From a methodological point of view, the article builds on empirical data acquired on the basis of exploring different practices in resolving hybrid conflicts.